POPULATION BIOLOGY OF SEABOB-SHRIMP Xiphopenaeus kroyeri (Heller, 1862) CAPTURED ON THE SOUTH COAST OF PERNAMBUCO STATE, NORTHEASTERN BRAZIL - Danilo Francisco Corrêa Lopes; Silvio Ricardo Maurano Peixoto; Flavia Lucena Frédou; Emanuell Felipe Beserra da Silva (Brazilian Journal of Oceanography, 2014)
This paper aims to describe the population dynamics and to evaluate the stock of the seabob-shrimp Xiphopenaeus kroyeri on the coast of Pernambuco. Sampling was carried out between August/2011 and July/2012 in Sirinhaém, southern coast of Pernambuco. A total of 1201 individuals were analyzed, 673 females and 528 males. Total length (Lt) of females varied from 4.5 to 13.5 cm while the Lt of males ranged between 4.0 and 11.0 cm. The relationship between the Lt and carapace length and Lt and total weight showed negative allometry (males, females and pooled sexes). The slope of the curve "b" was statistically different between males and females for both relationships. Females mature with 8.90 cm. Asymptotic length L∞ was lower for males than for females (12.26 to 14.79 and 10.72 to 11.5 cm, respectively), K was similar between sexes (1.00-2.04 and 1.00-2.63 cm/year-1 respectively) as well as the longevity and size at 1st capture (1.50 to 1.97) years and 7.9 to 8.9 cm for males and females, respectively). The results indicate that X. kroyeri in the region is not overexploited for males, however considering females and pooled sexes the stock is near to being fully exploited.